Imágenes de la Prisión en tiempo de guerra, 1812, 1912, 2012 - Zozaya-Montes, Maria (2013)
During the Peninsular Wars many napoleonic prisioners were token as captives to France. The non-commissioned officers, specially military engineers (lieutenants), were treated as elite prisoners. Then, they had a different way of life in prison as we use to imagine nowadays, even within the academic field, where there is a big gap on the subject. Normally those prisoners could move around the cities they were send and could go to the libraries and universities. So, sometimes the ways they lived that prison period was different as how it was spread in the common mentalities: First, after the conflict (1814); second, within the commemorations (1914), and third, one century later (2012), when it was assumed in the collective mentalities the traumatic experience of the concentration camps and the brutality of world war period (1930´s 1950´s). So, the image we use to have of that initial moments (1808- 1814) is quite different to the real one we show in this study.